Les zones de pêche protégées au Sénégal : entre terroir du pêcheur et parcours du poisson. Quelle(s) échelle(s) de gestion ? - Adama Mbaye; Ndiaga Thiam; Massal Fall (Développement Durable et Territoires)
The villages of Mballing, Nianing, Point Sarène and Mbodiène located on the « Petite Côte » of Senegal, intended to implement their own Protected Fishing Zone (PFZ). Fishermen define the PFZ according to empirical knowledge on fish biology but also on their means to insure the application of management rules on the PFZ. Surfaces covered do not exceed two kilometers offshore from the coastline. Support researches have shown that the narrowness of zones covered offshore, raised the relevance of the PFZ efficiency on the management of the species demersal targeted. Regarding the case of Petite Côte, the shallow rocky zones (2 to 3 m of depth) extend on 3-4 kilometers offshore. It has been recommended to establish common PFZ that covers at least 3 km offshore to include spawning and nursery area for the main targeted species. However, the scientific argument putting forward the fish area repartition, here in the sense of « path » [parcours], comes up against the community’s identification to their « local area » [terroir].